Historical Evidences of Traditional Sanskrit Teaching Among the Sri Lankan Tamils - Balakailasanathasarma, M. (University of Kelaniya, 2019)
Sanskrit is one of the ancient classical languages indescribably vast and rich and has its own literary tradition-poetic theory, grammar, aesthetics and etc. Sri Lanka has an enriched Sanskrit education over the years and currently it is institutionalized. Sri Lankan Tamils are natives of the South Asian island state of Sri Lanka. Most of Sri Lankan Tamils in Sri Lanka live in the Northern and Eastern provinces and majority throughout the rest of the country. Despite the fact that Sri Lankan Tamils have a rich tradition in Traditional Sanskrit Teaching, they did not actively engaged in documentation and presentation due to the unavoidable reasons. Teaching is ever changing process. Language teaching has been many chances in its pedagogical aspects. Education in Sri Lanka in its traditional form was closely related to religion. It is applicable to the Tamils too. Early oral traditions of the Upanishads, the guru-shishya relationship plays an important part in traditional Sanskrit teaching of Sri Lanka. In that tradition students were expected to follow strict monastic guidelines prescribed by the guru. By the colonial era the gurukula system was declining in Sri Lanka. After independence several gurukulas have begun, driven by a desire to uphold tradition and due to the influence of the Hinduism.Sanskrit tradition among the Sinhalese was studied by Pannasara.D (1958) and he lists the evidence of this tradition since from the early historical period and identified some epigraphically sources also. Wijesekara, O H De A (1951) studied the Sanskrit Education at the University level in Sri Lanka. In another study Sivasamy, V. (1992) highlights a bird's eye view of the contributions of Sri Lankan Tamils to Sanskrit. In view of above it is true that the Sanskrit represented a common foundation for the traditions of Sinhalese and Tamils of Sri Lanka from early times. The study specially focused on this area to make awareness among the Sanskrit scholars to study further. Objective of this study is to identify some historical evidences of Traditional Sanskrit Teaching among the Sri Lankan Tamils through cases studies and other historical evidences. Traditional Sanskrit learning system-teaching Sanskrit through Sanskrit is inevitable to get the command over Sanskrit even in the modern days. Since all the Sanskrit teachers of today are the products of grammar translation method, with very few expectations of those who studied in traditional and modern stream, most of them do not have the communicative skills in Sanskrit. So there is a need for a bridging both ancient and modern, and synthesizing of all the great thoughts through one language. This study suggest making necessary steps to preserve this tradition with the support of temples and other religious organizations.
Keywords: Education; Sri Lankan Tamils; Sanskrit Teaching; Sanskrit Tradition